Regional infrastructures, infrastructural regionalism. Issue 12 (2nd December 2019) - Glass, Michael R.; Addie, Jean-Paul D.; Nelles, Jen
ABSTRACT: An 'infrastructure turn' across the social and policy sciences is generating a new wave of interdisciplinary enquiry into how infrastructure is shaping urban and regional space. This editorial introduces a virtual special issue that charts the evolution of infrastructure as an empirical and conceptual concern within Regional Studies . The issue demonstrates that analysing regions through infrastructure – whether large, capital-intensive projects or more mundane infrastructures – provides a novel and necessary perspective on the regional question.